Investigation of Glutaric Anhydride as an Electrolyte Additive for Graphite/LiNi0.5Mn0.3Co0.2O2 Full Cells. Issue 2 (1st January 2017) - Peebles, Cameron; He, Meinan; Feng, Zhenxing; Su, Chi-Cheung; Zeng, Li; Bedzyk, Michael J.; Fenter, Paul; Wang, Yan; Zhang, Zhengcheng; Liao, Chen
Abstract : The effects of glutaric anhydride (GA) as an electrolyte additive for graphite/LiNi0.5 Mn0.3 Co0.2 O2 full cells operating between 3.0–4.4 V were investigated. Linear scan voltammetry (LSV) revealed that GA preferentially oxidized prior to the carbonate-based electrolyte while Li/graphite half cells revealed that GA can suppress electrolyte decomposition on the graphite electrode giving rise to the bifunctional nature of this additive. The addition of both 0.5 and 1.0 wt% of GA into the carbonate-based electrolyte resulted in superior cycling performance compared to the baseline electrolyte as demonstrated by the slight increase in initial capacities and significant increases in capacity retention over 117 cycles at C/3. Electrochemical impedance spectroscopy (EIS) showed that while the overall impedance of the GA containing cells was higher than the cells with the baseline electrolyte the change in impedance between post-formation and post-cycling was smallest for the cells containing GA. Additionally, X-ray photoelectron spectroscopy (XPS) analysis confirmed that GA decomposed on the cathode surface leading to an increase in oxygen-containing species, a decrease in LiF species and a simultaneous increase in Lix POy Fz species.